Differentiated approach at the choice of chronic hepatitis C antiviral therapy mode (real clinical practice experience) - I. Yu. Pirogova; N. B. Kovaleva; E. P. Patlusov; E. S. Radchenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of the study. To estimate efficacy and safety of cepeginterferon-alpha 2b (cPEG-IFNα2b) and ribavirin combination for the treatment of chronic hepatitis C (CHC), to define necessity of IL-28V genetic polymorphism diagnostics, to estimate liver elastometry scores at the background of antiviral therapy. Material and methods. Overall 164 patients with hepatitis C viruses (HCV) genotypes 1, 2 and 3 in 4 medical centers received antiviral therapy. All patients received cPEG-IFNα2band ribavirin. The treatment mode and dose of drugs conformed to the existing standards. Treatment response was defined by the frequency of sustained virologic response (SVR) achievement. All patients were included in the treatment safety analysis. Besides that, in 104 patients liver tissue elasticity scores dynamics was estimated according to elastometry data. Results. Results of double mode antiviral therapy (cPEG-IFNα2band ribavirin) at treatment of 164 CHC patients were analyzed: 58.5% (n=96) - patients had HCV genotypes 2-3, 41.5% (n=68) of patients - HCV genotype 1. The majority of the patients had mild fibrosis and low viral load. Overall SVR was achieved in 86.5% of patients (n=142). Of patients with HCV genotype 1 the rate of SVR was 79.4% (n=54), in patients with genotypes 2 and 3 - 91.7% (n=88). In patients with the IL-28V genotype variant C/C the SVR rate was 93.7% (n=45): in 100% of patients with HCV genotypes 2 and 3 and in 85.7% of patients with HCV genotype 1. In 83,7% of the patients included in the analysis no statistically significant dynamics of liver tissue density was noted. Conclusion. As administration of interferon-free treatment modes for most of patients is limited due to financial considerations, application of IFN-based modes of treatment in clinical practice is still actual. Results of the present study demonstrate that screening for treatment candidates allows to achieve high efficacy and favorable safety profile of double treatment mode (cPEG-IFNα2b and ribavirin).